Politique et justice dans un style déconstructif - E. Berns, Egid (Filozofski vestnik, 2016)
The paper »Politique et Justice« firstly explains how politics as hegemonic articulation of the social as conceptualized by Ernesto Laclau can be understood from a Derridean point of view, which is dominated by economic circularity. Secondly, by comparing the political conceptions of Laclau and Derrida, especially on the question of decisions in the terrain of undecidability, it criticizes Laclau’s pure decisionism and tries to establish how in a dcconstuctive style of thinking political decisionism is always caught up in an appeal for justice, which nevertheless exceeds it.